The Development and Evaluation of an index language for energy research [Volume 2] - Blomkamp, Yvonne (Institute for Monitoring and Evaluation, 2023)
Although numerous dictionaries of energy terms are available, and there are other thesauri on specific aspects of energy, for example, coal, biomass, nuclear energy, there are few comprehensive energy thesauri. So far, no energy thesaurus applicable to South Africa, has been published. It was found that energy terms in the US. Department of Energy's Energy Data Base: Subject Thesaurus are used in a different context to South Africa. The United Kingdom in - turn, used terms in a different context to the United States . In order for there to be effective cooperation between information centres engaged in the collection, storage and . dissemination of energy-related information in South Africa, a need was perceived for the definition and standardisation of the terms and concepts used in the energy field. In recognition of this need, the CSIR provided funds for a year to develop an energy thesaurus relevant to South Africa. As the Energy Research Institute at the University of Cape Town had the most developed energy information system in South Africa at the time, the vocabulary from the Institute's energy database was used as the base from which the thesaurus was constructed. The database contained information considered to be most representative of the main areas of research in the energy field in South Africa. Compilation was undertaken with the assistance and cooperation of the research staff at the Institute. The core area of the thesaurus is the energy field, with an emphasis on energy technology, energy research and development, energy sources, energy resources and reserves, and energy utilisation. A special emphasis is placed on alternative energy, which includes appropriate technology and alternative fuels. The fringe areas of the thesaurus are economics, engineering, and air pollution. The thesaurus has been designed for use mainly in a computerised information system, although it could be made available for use in a manual system. In a computerised system, it is hoped that, built into the system, it could be used for reference as an online aid to both indexers and searchers. It must be emphasised that this will not exclude the use of natural or free language in searching. Thus, the thesaurus can be used as a guide if and when required.